Research and applications on intelligent operations of cross-professional carrying network - Sai HAN; Dongyue ZHANG; Zelin WANG; Guangquan WANG; Ao LI; Qiukeng FANG; Hongbing MA (Dianxin kexue)
With the increasingly close integration of artificial intelligence technology and networks, the operation and production of networks in the future should be fully digitalized, automated and intelligent.At present, fault locating of cross-professional network mainly relies on operation and maintenance staff of each professional network to analyze and dispatch orders, resulting in long trouble clearing time and repeated orders.In order to save manual work, with the help of automation and artificial intelligent technologies, a cross-professional network intelligent operation and maintenance system was developed and applied in real network.The associated topology information of IPRAN and OTN, along with the real-time IPRAN and OTN alarm data were analyzed, the root cause alarm was located accurately, the fault location was determined, and dispatch order was achieved automatically.A automatic cross-professional fault diagnosis capability was built by the system, which reduced the fault locating time from traditional two minutes to tens of milliseconds, therefore, the manual work was reduced by more than 90%, and 95% fault types of the existing network could be covered.